2008
DOI: 10.1002/humu.20836
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inTREM2lead to pure early-onset dementia without bone cysts

Abstract: A genome-wide screen using 382 STR markers to localize and identify the gene implicated in early-onset dementia (EOD) without bone cysts in a Lebanese family with three affected subjects was conducted. A unique locus homozygous by descent at chromosome 6p21.2 locus was identified. Candidate genes were explored by fluorescent sequencing and the effect of the identified mutation was confirmed by qualitative and quantitative RT-PCR. The genetic analysis revealed a novel deletion, c.40+3delAGG, in the 5' consensus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(91 citation statements)
references
References 28 publications
(27 reference statements)
5
86
0
Order By: Relevance
“…In both models, peripheral, hematopoietic side effects are likely the main contributing factors of the lethal phenotype. Nevertheless, long-term elimination or dysfunction of microglia likely has deleterious consequences on CNS homeostasis as exemplified in neurodegenerative conditions, such as Nasu-Hakola disease or Rett syndrome (22,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In both models, peripheral, hematopoietic side effects are likely the main contributing factors of the lethal phenotype. Nevertheless, long-term elimination or dysfunction of microglia likely has deleterious consequences on CNS homeostasis as exemplified in neurodegenerative conditions, such as Nasu-Hakola disease or Rett syndrome (22,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…There has been a report of a case of a TREM2 gene mutation in a patient who manifested symptoms of dementia without exhibiting bone lesions (9). Similarly, there have been two reported cases of heterozygous carriers of the mutated allele of TREM2 gene mutation who had profound visuo-spatial memory impairment without exhibiting bone lesions and whose SPECT study revealed the diminished blood flow to the basal ganglia (19).…”
Section: Discussionmentioning
confidence: 99%
“…However, without such bone lesions, diagnosis can be very difficult. According to Chouery et al, some patients in whom the mutation of the TREM2 gene was present developed early-onset dementia without exhibiting bone lesions (9). In such patients, genetic testing may be needed to The testing was performed when the patient was 35 years old, before the onset of convulsive seizures.…”
Section: Introductionmentioning
confidence: 99%
“…11,12,21 Interestingly, loss-of-function mutations of either TREM2 or DAP12 are responsible for a chronic neurodegenerative disease named Nasu-Hakola. 33 Patients with mutations of TREM2 show as a major symptom pure early-onset dementia, 34 whereas patients with DAP12 mutations have dementia and bone cysts. 35 Here, we aimed to identify new microglial receptors that have a phagocytic ITAM signaling capacity and are involved in clearance of A␤ in AD.…”
Section: Discussionmentioning
confidence: 99%